Ornamental designs of Penang Chinese shophouses / Zhu Nianwei - Zhu , Nianwei (2019)
This paper is a study of ornament designs on the facade of Penang Chinese Shophouses. Most of these Shophouses were built between the years 1824-1957, during the period under the British administration. Thus, there are ornamentation and decoration of colonial style on the facade of these Shophouses that is rarely seen on present day Shophouses. The scope of study involves a few selected Chinese Shophouses located at Love lane, Jalan Muntri, Lebuh Armenian, Lorong Macaliser and Jalan Kedah. These Shophouses are selected according to their history, location and facade treatment. The studies on the selected buildings from the Penang Shophouses are in “Early Straits” Eclectic Styles and “Late Straits” Eclectic Style during 1890s-1930s. The study focuses on the doors, windows, vents, column, corbels and eaves of buildings. This research studies the functional and symbolic importance of the ornamental design found in Penang Chinese Shophouses in hopes of preserving the heritage of Penang Chines Shophouses. In the last 50 years, many of Southeast Asia cities have undergone rapid change due to the complicated political situation and the burgeoning economic development. Many Shophouses have been demolished to make way for construction of hotels and modern concrete office buildings in the 1970s -80s. Consequently the UNESCO1, World Heritage Committee has already put Penang on the list of the most-endangered heritage sites. The results showed the ornamental design of architectural of selected Shophouses, the history of the ornamental, the element of ornamental design of the building , the influence of ornamental designs and its origin, the functionality of the elements adopted in the climatic region, the essence of the ornamental, and the classification of architectural ornamental. The findings of architectural ornamental can be clearly divided into three basic categories: the mimetic ornament, the applied ornament, the organic ornament. The Shophouses facade analysed consists of ornamentations of various form, colours, meanings and expressions.